Virtue Politics as the PPP's Political Communication Strategy: A Framing Analysis of Petiga TV YouTube Content (Oratio Directa, 2025)
This study examines political Islam as a political communication strategy used by the United Development Party (PPP) in framing video content on YouTube, particularly on Petiga TV. It focuses on two videos, The Story of Hamzah Haz Leading the PPP and an Exclusive Interview with Acting PPP Chairman Muhamad Mardiono. The study uses a qualitative framing analysis to examine how the PPP employs political Islam to influence public perception through social media video. The findings indicate that the PPP uses political Islam as a communication strategy by constructing narratives about the party's role and contribution in upholding religious and Islamic values in Indonesian politics. This framing seeks to reinforce a positive party image, particularly among audiences interested in religious issues. The study also highlights YouTube's importance for disseminating political messages, especially among young voters who actively use social media.
Keywords: Political Islam; Political communication strategy; PPP; Content framing; Social media